Strength training prior to muscle injury potentiates low-level laser therapy (LLLT)-induced muscle regeneration. Issue 2 (February 2017) - Morais, Samuel; Goya, Alexandre; Urias, Úrsula; Jannig, Paulo; Bacurau, Aline; Mello, Wagner; Faleiros, Paula; Oliveira, Sandra; Garcia, Valdir; Ervolino, Edilson; Brum, Patricia; Dornelles, Rita
Abstract We evaluated whether strength training (ST) performed prior to skeletal muscle cryolesion would act as a preconditioning, improving skeletal muscle regeneration and responsiveness to low-level laser therapy (LLLT). Wistar rats were randomly assigned into non-exercised (NE), NE plus muscle lesion (NE + LE), NE + LE plus LLLT (NE + LE + LLLT), strength training (ST), ST + LE, and ST + LE + LLLT. The animals performed 10 weeks of ST (climbing ladder; 3× week; 80% overload). Forty-eight hours after the last ST session, tibialis anterior (TA) cryolesion was induced and LLLT (InGaAlP, 660 nm, 0.035 W, 4.9 J/cm2 /point, 3 points, spot light 0.028 cm2, 14 J/cm2 ) initiated and conducted daily for 14 consecutive days. The difference between intergroups was assessed using Student'st test and intragroups by two-way analysis of variance. Cryolesion induced massive muscle degeneration associated with inflammatory infiltrate. Prior ST improved skeletal regeneration 14-days after cryolesion and potentiated the regenerative response to LLLT. Cryolesion induced increased TNF-α levels in both NE + LE and ST + LE groups. Both isolated ST and LLLT reduced TNF-α to control group levels; however, prior ST potentiated LLLT response. Both isolated ST and LLLT increased IL-10 levels with no additional effect. In contrast, increased TA IL-6 levels were restricted to ST and ST + LE + LLLT groups. TA myogenin mRNA levels were not changed by neither prior ST or ST + LLLT. Both prior ST and LLLT therapies increased MyoD mRNA levels and, interestingly, combined therapies potentiated this response. Myf5 mRNA levels were increased only in ST groups. Taken together, our data provides evidences for prior ST potentiating LLLT efficacy in promoting skeletal muscle regeneration.